Current state of opioid stewardship. (1st April 2020) - Ardeljan, L Diana; Waldfogel, Julie M; Bicket, Mark C; Hunsberger, Joann B; Vecchione, Tricia Marie; Arwood, Nicole; Eid, Ahmed; Hatfield, Laura A; McNamara, LeAnn; Duncan, Rosemary; Nesbit, Todd; Smith, Jacob; et al.
Abstract: Purpose: The opioid epidemic continues to result in significant morbidity and mortality even within hospitals where opioids are the second most common cause of adverse events. Opioid stewardship represents one model for hospitals to promote safe and rational prescribing of opioids to mitigate preventable adverse events in alliance with new Joint Commission standards. The purpose of this study was to identify the prevalence of current hospital practices to improve opioid use. Methods: A cross-sectional survey of hospital best practices for opioid use was electronically distributed via electronic listservs in March 2018 to examine the presence of an opioid stewardship program and related practices, including formulary restrictions, specialist involvement for high-risk patients, types of risk factors screened, and educational activities. Results: Among 133 included hospitals, 23% reported a stewardship program and 14% reported a prospective screening process to identify patients at high risk of opioid-related adverse events (ORAEs). Among those with a prospective screening process, there was variability in ORAE risk factor screening. Formulary restrictions were dependent on specific opioids and formulations. Patient-controlled analgesia was restricted at 45% of hospitals. Most hospitals reported having a pain management service (90%) and a palliative care service providing pain management (67%). Conclusion: The absence of opioid stewardship and prospectively screening ORAEs represents a gap in current practice at surveyed hospitals. Hospitals have an opportunity to implement and refine best practices such as access to pain management specialists, use of formulary restrictions, and retrospective and prospective monitoring of adverse events to improve opioid use.